Law in everyday life - Sarat, Austin; Kearns, Thomas R. (Amherst series in law, jurisprudence, and social thought., 1993)
Sarat and Kearns . . . have edited a truly marvelous work on the impact of the law on daily life and vice versa. . . . the essays are all exemplary, thought- provoking works worthy of a long, contemplative read by scholars, lawyers, and judges alike. --Choice "The subject of law in everyday life is timely in theory and in practice. The essays collected here are stimulating for the very different ways in which they reconfigure the meanings of 'the law' as cultural practice, and 'the everyday' as a cultural domain in which the state expresses a range of interests and engagements. Readers looking for an introduction to this topic will come away from the book with a clear sense of the varied voices and modes of inquiry now involved in sociolegal studies, and what distinguishes them. More experienced readers will appreciate the book's meticulous reconsideration of the instrumentalities, agencies, and constructedness of law." --Carol Greenhouse, Indiana University Contributors include David Engel, Hendrik Hartog, Thomas R. Kearns, David Kennedy, Catharine MacKinnon, George Marcus, Austin Sarat, and Patricia Williams. Austin Sarat is William Nelson Cromwell Professor of Jurisprudence and Political Science, and Chair of the Department of Law, Jurisprudence, and Social Thought, Amherst College. Thomas R. Kearns is William H. Hastie Professor of Philosophy and Professor of Law, Jurisprudence, and Social Thought, Amherst College.